Development of 3A Perspectives to Assessment of Mosque Tourism Readiness: At-Taqwa Grand Mosque in Bengkulu City as Case - Agusti, Netta (STAI Terpadu Yogyakarta, 2023)
It was found that many past studies assessing tourism readiness, especially the profit sector, used the 3A perspective: attractions, amenities and accessibility. Unfortunately, existing studies are limited to testing without developing the concept. This research aims to develop indicators contained in the 3A perspective by assessing the readiness of the At-Taqwa Great Mosque in Bengkulu City as a halal tourism location. The case is dissected using qualitative work that relies on depth of information. Data collection utilized in-depth interviews, repeated observations, and online and offline documentation. All data is processed following the categorization determined from the start. This research found indicators that need to be considered for attractions in the form of permanent and temporary; amenities in the form of main tourism, supplementing tourism, and supporting tourism amenities; and accessibility in the form of access to services and transportation. The development of 3A can facilitate the work of practitioners and academics in assessing the readiness of halal tourism. Future studies need to continue this research by testing each indicator that has been developed.